Effects of dynamic change in fetuin-A levels from the first to the second trimester on insulin resistance and gestational diabetes mellitus: a nested case–control study. Issue 1 (20th January 2020) - Jin, Chuyao; Lin, Lizi; Han, Na; Zhao, Zhiling; Liu, Zheng; Luo, Shusheng; Xu, Xiangrong; Liu, Jue; Wang, Haijun
Abstract : Objective: To examine the effects of dynamic change in fetuin-A levels before the diagnosis of gestational diabetes mellitus (GDM) on insulin resistance and GDM. Research design and methods: A total of 135 women with GDM and 135 normal glucose tolerance (NGT) women with matched age (±2 years old) and gestational age at taking the oral glucose tolerance test (OGTT) were included in this nested case–control study. Fasting venous blood samples were collected at the prenatal visit of the first trimester and during OGTT of the second trimester. Plasma concentration of fetuin-A and insulin was determined. Results: The plasma fetuin-A concentration in women with GDM was significantly higher than NGT controls in both the first trimester (medians: 403.0 pg/mL vs 273.4 pg/mL; p<0.05) and the second trimester (medians: 475.7 pg/mL vs 290.8 pg/mL; p<0.05) and notably increased from the first to the second trimester. Multivariate linear regression analysis showed that the change in fetuin-A concentration was associated with the changes in fasting insulin, homeostasis model assessment (HOMA) of insulin resistance, and HOMA of β-cell function (HOMA-β) (p<0.05). The highest quartile of the increase in fetuin-A concentration from the first to the second trimester was associated with a higher risk of developing GDM compared with the lowest quartile (OR 2.14; 95% CI 1.05 to 4.37). Conclusions: The dynamic change in fetuin-A levels was associated with the changes in insulin resistance and β-cell function from the first to the second trimester, and was associated with an increased risk of the development of GDM, indicating that fetuin-A could be a biomarker to predict the risk of GDM. Trial registration number: NCT03814395 .